2022
DOI: 10.1002/ccr3.5315
|View full text |Cite
|
Sign up to set email alerts
|

Novel PKLR missense mutation (A300P) causing pyruvate kinase deficiency in an Omani Kindred—PK deficiency masquerading as congenital dyserythropoietic anemia

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…3 Finally, recent investigations have revealed that a significant proportion of patients initially suspected of CDA I or II, based on both hypo-productive anemia and bone marrow morphological characteristics (Figure 2), were ultimately diagnosed with chronic anemia due to enzymatic defects, mainly pyruvate kinase deficiency (PKD) due to PKLR mutations. 12,34 To note, the presence of inadequate reticulocytosis, erythroblasts in peripheral blood, or immature forms at bone marrow examination, are frequently observed in patients with severe PKD. 35 Furthermore, evaluation of the main regulators of iron balance and erythropoiesis, that is, EPO, erythroferrone (ERFE), and hepcidin, showed comparable levels between CDA and PKD patients, 36 thus explaining the misdiagnosis between these conditions.…”
Section: Isolated Formsmentioning
confidence: 99%
“…3 Finally, recent investigations have revealed that a significant proportion of patients initially suspected of CDA I or II, based on both hypo-productive anemia and bone marrow morphological characteristics (Figure 2), were ultimately diagnosed with chronic anemia due to enzymatic defects, mainly pyruvate kinase deficiency (PKD) due to PKLR mutations. 12,34 To note, the presence of inadequate reticulocytosis, erythroblasts in peripheral blood, or immature forms at bone marrow examination, are frequently observed in patients with severe PKD. 35 Furthermore, evaluation of the main regulators of iron balance and erythropoiesis, that is, EPO, erythroferrone (ERFE), and hepcidin, showed comparable levels between CDA and PKD patients, 36 thus explaining the misdiagnosis between these conditions.…”
Section: Isolated Formsmentioning
confidence: 99%